Analysis of the Role of Shear Wave Elastography in Diagnosing Focal Liver Lesions - Soban Shahid, Sahar Javed, Mustafa Ali Siddiqi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Focal hepatic lesions are the second leading cause of death in men worldwide. However, shear wave elastography (SWE) has proved to help assess liver fibrosis. We aim to demonstrate the role of shear wave elastography in the diagnosis of focal liver lesions. Methods: A prospective study was conducted in the radiology department of CPEIC Multan from April 2021-April 2022. A total of 70 patients with 93 focal lesions were included. Shear wave elastography (SWE) was performed on all the patients, and local lesions and parenchyma stiffness values were calculated. Ten patients were excluded as they failed elastography acquisitions. Contrast-enhanced CT and MRI were performed on the remaining 60 patients. Thirty-two patients underwent liver biopsy. Benign focal lesions were confirmed by analyzing the results of ultrasound biopsy, CT, and MRI. Results: Cholangiocarcinoma was found to have the highest stiffness value (34.2kPa), hence the stiffest malignant lesion. Focal nodular hyperplasia had a stiffness value of 25.4kPa and was the most stiff benign lesion. The average stiffness value between malignant and benign lesions had a significant difference, the value of malignant lesions being significantly high ( p<0.001). Conclusion: Shear wave elastography can efficiently differentiate between malignant and benign hepatic lesions and can individually characterize these lesions accurately. Keywords: Focal liver lesions, malignant, stiffness value, shear wave elastography, benign